Circulatory Stasis or Thrombus in Left Atrial Appendage, An Easy Diagnostic Solution. Issue 3 (May 2019) - Kantarci, Mecit; Ogul, Hayri; Sade, Recep; Aksakal, Enbiya; Colak, Abdurrahim; Tanboga, Ibrahim Halil
Abstract : Objective: The purpose of this study was to assess the diagnostic performance of prone position cardiac multidetector computed tomography (MDCT) in the detection of left atrial appendage (LAA) thrombi and to make differentiate between thrombus and circulatory stasis using transesophageal echocardiography (TEE) as the criterion-standard imaging modality. Methods: From December 2014 to April 2016, 53 consecutive patients were admitted to the hospital because of circulatory stasis or/and thrombus. All patients underwent prone-position MDCT and TEE. Prone-position MDCT and TEE sensitivity, specificity, positive predictive value, and negative predictive value were calculated. Results: For the MDCT scan in the prone position, the sensitivity, specificity, positive predictive value, and negative predictive value results were 100%, 100%, 100%, and 100%, respectively. Conclusions: Multidetector computed tomography scanning in the prone position differentiates circulatory stasis and LAA thrombus, is clinically useful for detecting and ruling out LAA thrombus, and may be an alternative to TEE as a diagnostic tool.